Motivación académica y expectativas profesionales en estudiantes: Una revisión sistemática - Rojas Virijivich, Rodolfo Franco (2023)
Motivation is the engine of all human action. It is one of the most important factors for choosing and successfully studying a professional career. The moment of choosing a vocation in the life of a young person is decisive and is made on the basis of limited information and experience. In this sense, determining the academic motivations and professional expectations of students is extremely interesting since they involve personal, social and contextual factors about individuals and careers. This paper aims to develop a systematic review of the literature that studies academic motivation and career expectations. However, it is also an extension and development of an existing systematic review: Factors Related to University Students' Motivation and Instruments for Its Evaluation: A Systematic Review (Sanchez and Martinez, 2022). For the analysis we searched the Web of Science, Scopus, Scielo and RedALyC databases for the terms "academic motivation" and "professional expectations". Seventy-nine articles were found that met the criteria proposed for the research. These articles were published between 2009 and 2022.